The Rise of Latina Culture and the Political Economy of English in Kansas: Perceptions of Adult Learners - Jeff Zacharakis; Gabriela Diaz de Sabates (Adult Education Research Conference, 2008)
This research is drawn from two focus groups—one with Latina college students and the other with Latinas attending a Kansas City, KS, adult-learning center.
Keywords: English as a second language; Latina; and political economy